2022
DOI: 10.3390/ijerph19084471
|View full text |Cite
|
Sign up to set email alerts
|

Association between Internalized Stigma and Depression among People Living with HIV in Thailand

Abstract: Internalized stigma and depression are among the most common mental health problems in people living with HIV (PLHIV). This study aimed to examine the association between depression and overall internalized stigma, as well as different aspects of internalized stigma in PLHIV. The study included 400 PLHIV receiving care in Bangkok and Chiang Mai, Thailand. Data were analyzed using descriptive statistics, Mann-Whitney U test, and Spearman correlation coefficients. The results indicated the PLHIV with mild depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…HIV-related stigma was identified as a barrier to HIV testing and treatment, as has been noted elsewhere ( 62 , 63 ). Similarly, our findings match previous work that internalised stigma limits social networks and reduces the social interaction of PLWHA due to self-imposed social isolation, self-exclusion, and the avoidance of negative judgment, guilt, and shame associated with HIV infection ( 64–66 ).…”
Section: Discussionsupporting
confidence: 91%
“…HIV-related stigma was identified as a barrier to HIV testing and treatment, as has been noted elsewhere ( 62 , 63 ). Similarly, our findings match previous work that internalised stigma limits social networks and reduces the social interaction of PLWHA due to self-imposed social isolation, self-exclusion, and the avoidance of negative judgment, guilt, and shame associated with HIV infection ( 64–66 ).…”
Section: Discussionsupporting
confidence: 91%
“…At the same time, stigma may lead to daily communication difficulties and loss of social skills [ 27 ]. Many studies have shown that compared with the subjects in the standard group, the patients with stigma show a significantly higher tendency to depression [ 28 , 29 ]. Therefore, low-level stigma is an essential factor in improving depression.…”
Section: Introductionmentioning
confidence: 99%
“…The HPH group also experienced psychological distress owing to HIV-related stigma or multimorbidity for many years (20,43). Some studies have suggested an association between HIV-related stigma and psychological distress or mood (44,45). Long-term experiences of HIV-related stigma could have prevented HPH from connecting with people and society, affected various life events such as employment and marriage, (P6) and reduced their vigor.…”
Section: Discussionmentioning
confidence: 99%